Interface Structure and Evolution of Dinaphthothienothiophene (DNTT) Films on Noble Metal Substrates. Issue 21 (19th September 2018) - Dreher, Maximilian; Bischof, Daniel; Widdascheck, Felix; Huttner, Andrea; Breuer, Tobias; Witte, Gregor
Abstract: Dinaphthothienothiophene (DNTT) is a promising new organic semiconductor which combines high charge carrier mobility with chemical robustness. Although the properties of organic electronic devices are largely determined by the interfaces with electrodes, the interface between DNTT and metals is hardly studied so far. Here, the interface structures of DNTT on Ag(111) and multilayers are examined and they are compared with films grown on polycrystalline and (111) surfaces of silver and gold. In the seedlayer regime, two different interface structures formed by exclusively flatlying molecules and a herringbone arrangement are identified for increased coverages. Combining low energy electron diffraction, scanning tunneling microscopy, and X‐ray absorption measurements, precise structure data for both phases are derived and their respective adsorption energies are determined to explain why both phases are formed. On all examined surfaces, DNTT multilayers consist of discrete fibers reflecting a notable dewetting but exhibit different molecular orientations: Molecules are recumbently arranged on the (111) surfaces, but uprightly oriented on polycrystalline surfaces. Complementary work function measurements yield rather similar values for DNTT monolayers on single‐ and polycrystalline metal substrates, while distinct differences are found for thicker films. The results appear important for improved transistor geometries, in particular vertical field‐effect transistors. Abstract : Thin films of the novel organic semiconductor dinaphthothienothiophene (DNTT) are investigated. Two different interface phases are observed on Ag(111) surfaces exhibiting distinctly different molecular structures and energetics. Moreover, the film structure of thicker layers as present in electronic devices based on DNTT is investigated on (111)‐faced gold/silver and polycrystalline metals as used as electrical contacts in devices.